2003
DOI: 10.1016/s1470-0328(02)01929-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of nitric oxide synthase by human umbilical vein endothelial cells: the effect of fetal plasma from pregnancy with umbilical placental vascular disease

Abstract: Objective To determine whether endothelial cell injury would be produced by factor(s) released into the fetal circulation, manifested by altered messenger RNA expression of nitric oxide synthase. Design Case -control study.Setting University teaching hospital.Samples Fetal plasma was collected from 34 normal pregnancies, 44 pregnancies with umbilical placental vascular disease identified by an abnormal umbilical Doppler and 11 pregnancies with maternal pre-eclampsia but with normal umbilical Doppler studies. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…T-cell anergy to fetal antigens has been associated with the IL-10 regulatory and tolerant properties of decidual macrophages ( 29 ). IL-10 therapy of T. gondii infections reduces trophoblasts apoptosis at the maternal–fetal interface and improves pregnancy outcomes ( 38 , 39 ). Decidual macrophage LILRB4 ligation by FcγRI inhibited TNF-α production and hampered functional activation ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…T-cell anergy to fetal antigens has been associated with the IL-10 regulatory and tolerant properties of decidual macrophages ( 29 ). IL-10 therapy of T. gondii infections reduces trophoblasts apoptosis at the maternal–fetal interface and improves pregnancy outcomes ( 38 , 39 ). Decidual macrophage LILRB4 ligation by FcγRI inhibited TNF-α production and hampered functional activation ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells in different beds do vary in the capacity to express adhesion proteins. We have previously shown that the expression of nitric oxide synthase mRNA is increased in endothelial cells induced by factor(s) released into the fetal circulation in umbilical placental vascular disease 7 . Nitric oxide has been reported to inhibit the induction of VCAM-1 expression by endothelial cells stimulated by factors such as cytokines 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation and consumption also occurs in this group. We have shown that plasma from fetuses with Doppler evidence of umbilical placental vascular disease contains factor(s) that induces endothelial cell apoptosis and up-regulates mRNA expression of nitric oxide synthase 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Giannubilo and colleagues [30] found that eNOS protein levels negatively correlate with the pulsatility Index (PI) determined by Doppler ultrasound, whilst iNOS levels in IUGR placental endothelium show a positive correlation with PI. Additionally, normal HUVEC exposed to PE-derived umbilical plasma show higher iNOS expression [176]. Under these conditions increased levels of nitrosative stress have been described [99].…”
Section: Placental Vascular Reactivity and Nitric Oxide Synthesis In mentioning
confidence: 96%